The Multifaceted Benefits of Leptin: Beyond Weight Regulation - Kinjal P. Patel, (Asian Journal of Pharmaceutics (AJP), 2024)
Leptin is a hormone that is produced by a variety of different cells, most notably adipocytes, but also by the stomach, lungs, and other organs, which mainly acts on the brain’s hypothalamus. Since its discovery in 1994, leptin’s pleiotropic activities have attracted increased interest from the scientific community. As a result, many pathological states have been related to leptin signaling disturbance. This includes the connection between one’s nutritional state and one’s immune competence, which is one of the functions listed. It shares structural similarities with other inflammatory cytokines such as IL-6 and IL-12. Leptin regulates immunological responses, which is consistent with its structure as a cytokine. Leptin’s most crucial physiological function is probably as a signal for the transition between the fasted and fed states. Although leptin may play a role in preventing obesity in some people, the prevalence of obesity is strongly correlated with elevated leptin levels. There are no human studies specifically designed to investigate the role of leptin, despite numerous reports of connections between leptin levels and various physiological and pathological states. In this review, the effect of leptin on different organ systems is described along with biology, mechanism of action, and its resistance factor.